PELAKSANAAN PENGELOLAAN HUTAN MANGROVE DALAM MEWUJUDKAN RUANG TERBUKA HIJAU DI KOTA DENPASAR - Eka Sugina Ariawan, Putu; Arya Utama, I Made; Dalem Dahana, Cokorda (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015, 2015)
Forest Park (Tahura) is defined as forest conservation which its is to functionprevents abrasion caused by the waves on the coast . Mangroves are located in the cityof Denpasar area with 700 hectares . Because of the importance of mangrove forests asa function of spawning fish in the waters , land protection from erosion by waves , windprotector of the land , and sea water filter istrusi to the mainland , then this article willdiscuss the Denpasar Government authorities related to the control and management ofmangrove forests . The research is empirical juridical research . Denpasar GovernmentAuthority relating to the control and management of mangrove forests fall under Article40 paragraph ( 1 ) , ( 2 ) and ( 3 ) Regional Regulation No. 27 Denpasar 2011concerning Spatial Plan Year 2011-2031 Denpasar these provisions are based andcorresponds to the central government laws on Article 59 to Article 65 of Law No. 41 of1999 on Forestry and on Article 63 of Law 32 of 2009 on Protection and Managementof Environment and must remain coordinated between the central government ,provincial governments and government area in accordance with article 6 and 7 ofGovernment Regulation No. 38 Year 2007 About the Governmental Affairs between theGovernment , Provincial Government , and the Government of Regency / City.
Keywords: Mangrove Forests, Green Open Space, Management